(untitled) (Journal of Engineering, 2023)
The presence of construction wastes such as clay bricks, glass, wood, plastic, and others in large quantities causes serious environmental problems in the world. Where these wastes can be used to preserve the natural resources used in construction and reduce the impact of this problem on the environment, it also works to reduce the problem of high loads of concrete blocks. Clay bricks aggregate (AB) can be recycled as coarse aggregate and replaced with volumetric proportions of coarse aggregate by ( 5% and 10%), as well as the use of clay brick powder (PB) by replacing its weight of cement (5% and 10%) and reduced in the manufacture of concrete blocks (blocks). Four mixtures will be prepared and tested to learn how to reuse the brick coarse aggregate ACB and PB powder brick as substitute materials for producing concrete blocks, use the water spray method to treat concrete building blocks (blocks) and check the Dimensions and compressive strength, and absorption.